Has Money Always Made the Sporting World Go Round? A Re-Interpretation of Early Commercialisation and Sport and Its Implication for Asian Sports History. Issue 2 (4th May 2022) - Vamplew, Wray
Abstract: This article argues that sport and commerce have a long historical relationship and challenges Asian sports historians to search for similar connections in the non-western world by using new definitions of commercialisation and entrepreneurship.